A COMPARATIVE STUDY OF EFFICACY AND TOLERABILITY OF ORIGINAL AND GENERIC SIMVASTATIN IN PATIENTS WITH HYPERLIPIDEMIA - V. P. Voronina; S. N. Tolpygina; N. P. Kutishenko; N. A. Dmitrieva; Yu. V. Lukina; S. Yu. Martsevich (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study efficacy and tolerability of original and generic simvastatin in patients with hyperlipidemia. Material and methods. Patients (6 men and 24 women) aged 38 to 77 years, which needed in lipid-lowering therapy were included into the open, crossover , randomized, comparative study of efficacy and tolerability of original and generic simvastatin. The drug effects on the blood levels of total cholesterol (TC), high density cholesterol (HDC), triglycerides (TG), low density cholesterol (LDC), and tolerability of treatment were evaluated. The treatment duration (with a change of medications) was 12 weeks. Results. The target levels of LDC after 8 weeks of treatment with both generic and original simvastatin (20 mg/day) were achieved in 10 (71.4%) patients in each group. After 8 weeks of therapy with generic and original simvastatin TC decreased from 6.4±0.8 to 4.4±0.6 mmol/l (p<0.001) and from 6.0±0.7 to 4.1±0.7 mmol/l (p<0.001), respectively. LDC levels decreased from 4.4±0.7 to 2.4±0.4 mmol/l (p<0.001) and from 4.2±0.7 to 2.2±0.6 mmol/l (p<0.001), respectively. Both simvastatin medications led to similar changes in blood lipid spectrum and had comparable tolerability. Conclusion. The lipid-lowering effect of the generic simvastatin is comparable to this of original simvastatin. That means generic medication is therapeutically equivalent to original one.